Enhanced aggressiveness of benzopyrene‐induced squamous carcinomas in transgenic mice overexpressing the proprotein convertase PACE4 (PCSK6). Issue 10 (21st May 2014) - Bassi, Daniel E.; Cenna, Jonathan; Zhang, Jirong; Cukierman, Edna; Klein‐Szanto, Andres J.
Abstract : PACE4 (PCSK6) is a proprotein convertase (PC) capable of processing numerous substrates involved in tumor growth, invasion, and metastasis. Because of the human relevancy of the tobacco‐associated carcinogen benzo[a]pyrene (B(a)P) we investigated whether transgenic mice in which this PC is targeted to the epidermis (K5‐PACE4) may be more susceptible to B(a)P complete carcinogenesis than wild type (WT) mice. In an in vitro experiment, using cell lines derived from skin tumors obtained after B(a)P treatment, we observed that PACE4 overexpression and activity accounts for an increased proliferation rate, exaggerated sensitivity to the PC inhibitor CMK, and interference with IGF‐1R autophosphorylation. Squamous cell carcinomas, obtained from K5‐PACE4 mice subjected to complete chemical carcinogenesis, were characterized by a 50% increase in cell proliferation, when compared with similar tumors from WT mice. In addition, tumors from K5‐PACE4 mice showed deeper invasion into the underlying dermis. Thus, mice overexpressing PACE4 exhibited tumors of increased growth rate and invasive potential when exposed to the human carcinogen B(a)P, further supporting the significance of PCs in tumor growth and progression. © 2014 Wiley Periodicals, Inc.